2019
DOI: 10.1021/acs.jnatprod.9b00205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-Deoxynojirimycin Isolated from Mulberry Leaves on Glucose Metabolism and Gut Microbiota in a Streptozotocin-Induced Diabetic Mouse Model

Abstract: 1-Deoxynojirimycin (DNJ) exerts hypoglycemic effects. However, the traditional method for DNJ extraction is inefficient, and the hypoglycemic mechanism of DNJ remains unclear. In this study, the mixed fermentation by Lactobacillus fermentum and Saccharomyces cerevisiae was used to enhance DNJ extraction efficiency. It was found that this strategy was more efficient than the traditional method as the yield improved from the original 3.24 mg/g to 5.97 mg/g. The purified DNJ significantly decreased serum glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…Recently, several investigations have reported that DNJ or DNJ-enriched mulberry leaf extracts markedly altered gut microbial community to improve metabolic diseases by promoting the growth of Akkermansia spp. and SCFA-producing genera such as Bifidobacterium , Lactobacillus , and Alistipes ( 24 , 38 , 39 ). In particular, DNJ was reported to enrich the abundance of Akkermansia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several investigations have reported that DNJ or DNJ-enriched mulberry leaf extracts markedly altered gut microbial community to improve metabolic diseases by promoting the growth of Akkermansia spp. and SCFA-producing genera such as Bifidobacterium , Lactobacillus , and Alistipes ( 24 , 38 , 39 ). In particular, DNJ was reported to enrich the abundance of Akkermansia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al found that mulberry leaf powder could alleviate the pathological conditions of streptozotocin-induced diabetic rats and modulate intestinal microflora [ 9 ]. In addition, Hu et al discovered that the compound 1-Deoxynojirimycin isolated from mulberry leaves could significantly decrease serum glucose and insulin levels while improving serum lipid levels and reversing insulin resistance in streptozotocin-induced diabetic mice [ 13 ]. The effects of mulberry leaf on blood glucose response were also tested in healthy and diabetic human subjects, which confirmed that blood glucose levels were markedly reduced by mulberry leaf ingestion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al . studied the hypoglycemic effect of 1‑deoxynojirimycin, isolated from mulberry leaves, and found that it promoted the growth of beneficial bacteria, such as lactic acid‐generating bacteria, and inhibited that of harmful bacteria, thereby improving the intestinal microbial composition and alleviating intestinal disorders in diabetic mice (Hu et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It plays an important role in the intake of nutrients, the growth and development of cells, and metabolism of the host (Rad et al, 2017), and accumulating data show that it may mediate some of the effects of anti-diabetic therapies (Min et al, 2009;Zhao et al, 2016). For example, Hu et al studied the hypoglycemic effect of 1-deoxynojirimycin, isolated from mulberry leaves, and found that it promoted the growth of beneficial bacteria, such as lactic acid-generating bacteria, and inhibited that of harmful bacteria, thereby improving the intestinal microbial composition and alleviating intestinal disorders in diabetic mice (Hu et al, 2019).…”
Section: Effect Of Dfms On the Diversity Of The Gut Microbiotamentioning
confidence: 99%